2020
DOI: 10.1016/j.ymgme.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation modifies the course of Niemann-pick disease, type C1 in a gender specific manner

Abstract: Niemann-Pick disease, type C1 (NPC1) is a rare neurodegenerative lysosomal storage disease with a wide spectrum of clinical manifestation. Multiple genetic factors influence the NPC1 mouse phenotype, but very little attention has been given to prenatal environmental factors that might have long-term effects on the neuroinflammatory component of NPC1 pathology. Studies in other mouse models of cerebellar ataxia have shown that developmental exposures lead to Purkinje neuron degeneration later in life, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…No obvious differences were seen between the Pcsk9 +/+ and Pcsk9 +/mice and these data were combined as Pcsk9 ctrl . Single knockout Npc1 -/-/Pcsk9 ctrl male (n = 10) and female (n = 14) mice had an initial normal, but slightly reduced, weight-gain followed by weight loss starting at about 6-7 weeks of age as expected for the Npc1 -/phenotype [44,45]. In the double knockout Npc1 -/-/Pcsk9 -/mice, both male (n = 6) and female (n = 7) mice were similar to the Npc1 -/-/Pcsk9 ctrl mice, showing a similar weight loss pattern consistent with the phenotype of Npc1 -/mutant mice alone ( Figure 1A,B).…”
Section: Knockout Of Pcsk9 Did Not Significantly Alter Weight Progresmentioning
confidence: 68%
“…No obvious differences were seen between the Pcsk9 +/+ and Pcsk9 +/mice and these data were combined as Pcsk9 ctrl . Single knockout Npc1 -/-/Pcsk9 ctrl male (n = 10) and female (n = 14) mice had an initial normal, but slightly reduced, weight-gain followed by weight loss starting at about 6-7 weeks of age as expected for the Npc1 -/phenotype [44,45]. In the double knockout Npc1 -/-/Pcsk9 -/mice, both male (n = 6) and female (n = 7) mice were similar to the Npc1 -/-/Pcsk9 ctrl mice, showing a similar weight loss pattern consistent with the phenotype of Npc1 -/mutant mice alone ( Figure 1A,B).…”
Section: Knockout Of Pcsk9 Did Not Significantly Alter Weight Progresmentioning
confidence: 68%
“…For example, Bianconi’s group 131 showed that female Npc1 mutant mice (BALB/c npc nih ) live significantly longer (median survival of 78 days) than male Npc1 mice (median survival of 66 days). In 2020, Cougnoux’s group 132 reported similar data on the C57BL/6J background. The mean survival was 65 ± 7 days and 55 ± 16 for C57BL/6J female and male mutant mice, respectively.…”
Section: Other Factors That Could Contribute To Phenotypic Variabilit...mentioning
confidence: 82%
“…The average survival previously reported for these mice ranges between 70 and 90 days 135 . On top of this, Cougnoux and colleagues 132 reported that in their facility, the Npc1 nih/nih mice in the C57BL/6J genetic background lived 61 ± 12 days and had a predominantly neurological phenotype with loss of cerebellar Purkinje neurons in C57BL/6J Npc1 nih/nih mice, like that observed in Npc1 nih/nih BALB/c mice. However, as mentioned above, Parra and colleagues have reported that these mice lived 32 days 71 and had a predominantly visceral phenotype.…”
Section: Other Factors That Could Contribute To Phenotypic Variabilit...mentioning
confidence: 93%
“…Numerous double mutant mice have been created to test whether and how specific candidate genes impact the disease [163,173,177,190,191,[219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235]. Sex-dependent differences in behavior [236], life span [37,134], and responses to immune activation [237] and to potential therapies [171,238] were reported in some NPC1 mutant mice, raising the question of whether sex is a modifying factor in NPC disease [37] as in other cholesterol-related pathologies [239][240][241][242] and normal cholesterol homeostasis [243,244].…”
Section: Mammalian Modelsmentioning
confidence: 99%